Urgency of Funds in the Management System of Educational Institutions - Ramli, Sahudi; Hapzi Ali; Kasful Anwar (Dinasti International Journal of Digital Business Management, 2023)
Education funding is the rupiah value of all resources (inputs) used for an educational activity. Thus, the problem is how can we save education funds in schools, so that with existing funds we can carry out educational activities of optimal quality and can improve the quality of learning. According to the 2003 National Education System Law, the government, local government and the community handle funding for education in Indonesia from an allocation of 20% of the APBN and APBD. All use of education funds must go through formal controls and non-formal controls.